Atmospheric dry deposition processes of particles on urban and suburban surfaces: Modelling and validation works. (1st October 2019) - Giardina, M.; Donateo, A.; Buffa, P.; Contini, D.; Cervone, A.; Lombardo, C.; Rocchi, F.
Abstract: Dry deposition process is one of the important pathways for the removal of particles from atmosphere. It is the result of a combination of different environmental and physical factors as atmospheric conditions, particle properties, characteristics of the canopy. For this latter factor, urban canopy represents unevenly combinations of different types of surface elements that increases the complexity of deposition process phenomena. Therefore, particle dry deposition on urban surfaces is not easy to configure and, although empirical or semi-empirical models in literature have been developed to address this aspect, there is not standardized and commonly accepted criteria, especially for submicron particles. In this paper, comparisons of different dry deposition models and measurement data by experimental campaigns, covering for different surface roughness conditions, i.e. from four Italian cities and urban environments of other countries, are performed. Giardina et al. (2017b) model, by using a Brownian diffusion resistance as proposed in this paper, seems to capture the main dry deposition processes for the examined contexts. Highlights: A pathway to remove pollutants in atmosphere is the dry deposition process. Modelling of dry deposition phenomena over urban canopies is performed. Comparisons were performed between deposition velocity models and experiments covering for different surface roughness conditions. The proposed Brownian diffusion resistance captures the main dry deposition processes for the examined urban canopies.